Thermo-expandable microspheres strengthened polydimethylsiloxane foam with unique softening behavior and high-efficient energy absorption - Cai, Jie-Hua; Huang, Ming-Lu; Chen, Xu-Dong; Wang, Ming (Applied surface science, 2021)
[Display omitted] •Controllable elastomer foams were achieved by adding TEHMs in PDMS.•The foams exhibited higher compression modulus and storage modulus than neat PDMS.•The foams had unique softening behavior due to the collapse of TEHMs during compression.•The stress of the foams could be partly recovered by the thermal treatment.•The softening behavior endowed the foams have good toughness and energy absorption. Herein, a simple and controllable foaming method was used to prepare the polydimethylsiloxane (PDMS) foams with high compressive resistance and motion-energy absorption efficiency. The thermo-expandable hollow microspheres (TEHM) expanded in PDMS matrix to form the TEHM/PDMS foams, which exhibited strengthened mechanical properties with unique softening behavior and high energy absorption property. The compressive curves of the TEHM/PDMS foams under small, medium and large strain were investigated to evaluate the softening behavior. Specifically, the TEHM/PDMS (1:2) foams had a compressive modulus of 10.2 MPa and a compression strength of 0.8 MPa, while neat PDMS showed only 4.3 MPa in modulus and 0.5 MPa in strength at 10% strain. However, after the large compression of 70%, the modulus decreased from 10.2 MPa to 2.5 MPa, which only was 25% of the initial value. Furthermore, the high ideal efficiency of motion-energy absorption of 38.3% was obtained in the TEHM/PDMS (1:2) foams while neat PDMS only got 15.8% at 70% strain. The softening phenomenon and high motion-energy absorption were ascribed to the step-by-step broken of TEHMs. The softening performance endows the foams with good toughness and consumes the impacted energy efficiently, providing a new horizon to broaden the application in anti-impacted and damaged area.